SCREENING OF PHOSPHATE SOLUBILIZING MICROORGANISMS COLLECTED FROM POST TIN MINING: POTENCY FOR FUTURE MINING REHABILITATION - Dewi Wulandari, S.Hut., M.Agr., Ph.D; Risa Rosita; Ahdiar Fikri Maulana (Teknik Lingkungan Universitas Islam Indonesia, 2023)
Tin mining produced massive tailings which dispersed across the land in the post-tin mining area, transforming the landscape into a hilly or basin landscape. The dominated white silica sand in this area is prone to erosion from water and wind, resulting in soil nutrition deficiency, meanwhile, heavy metal levels were found to be elevated. This condition makes it difficult for organisms to live in such a degraded post-tin mining area. Phosphate solubilizing microorganisms (PSM) contribute to phosphate availability by dissolving both fertilizers and bounded P in soil. This study aimed to select indigenous PSM collected from post-tin mining areas. Zea mays spp., the tested plant, was grown in sterilized sand to avoid the possible nutrient content, particularly phosphate, in the soil. Rock phosphate Granufos (containing 20% P2O5) was applied in sterilized sand (v: v= 1:100) as the source of limited and insoluble P. The 17 indigenous PSM were tested by inoculating them into Zea mays spp. growing in sterilized sand. Non-inoculated Zea mays spp. were prepared as well as control. Inoculation of 17 indigenous PSM significantly had higher soil available phosphor in comparison to control. Two PSM of P7 and P15 significantly had higher shoot concentrations among treatments. The isolate of P5 had the highest shoot dry weight among treatments. Overall, all PSM inoculations improved growth performance due to increased soil available P and improved shoot P uptake. These findings suggest that indigenous PSM potentially fills nutrient deficiencies, particularly P as a macronutrient needed to rehabilitate degraded post-tin mining areas.